Embodying cognition: working with self-control in cerebral palsy. (28th November 2016) - Martiny, Kristian Moltke; Aggerholm, Kenneth
Abstract: During the last decades, research on cognition has undergone a reformation, which is necessary to take into account when evaluating the cognitive and behavioural aspects of therapy. This reformation is due to the research programme called Embodied Cognition (EC). Although EC may have become the theoretical authority in current cognitive science, there are only sporadic examples of EC-based therapy, and no established framework. We aim to build such a framework on the aims, methods and techniques of the current third-wave of CBT. There appears to be a possibility for cross-fertilization between EC and CBT that could contribute to the development of theory and practice for both of them. We present a case-study of an EC-based model of intervention for working with self-control in cerebral palsy. We centre the results of the study and its discussion on how we should understand and work with self-control in a more general sense from both an EC and a CBT perspective. We end by elaborating the five learning objectives and present suggestions for follow-up reading.